Kovacikia euganea sp. nov. (Leptolyngbyaceae, Cyanobacteria), a new chlorophyll f producing cyanobacterium from the Euganean Thermal District (Italy) - Zampieri, Raffaella Margherita; Bizzotto, Edoardo; Campanaro, Stefano; Caldara, Fabrizio; Bellucci, Micol; La Rocca, Nicoletta (Frontiers in Microbiology, 2025)
Hot springs are considered modern terrestrial environments analogous to Archean continental surfaces, where photosynthetic life could have evolved. In this habitat cyanobacteria dominate thanks to the adaptations to high temperature and the capability to acclimate to low light intensity and far-red enriched spectra typical of microbial biofilms. The isolation and characterization of new cyanobacterial species from these environments is fundamental to discover genetic and physiological traits allowing them to thrive under such unfavorable conditions, giving useful information to understand the evolution and plasticity of oxygenic photosynthesis as well as to assess their metabolic biodiversity for biotechnological purposes. In this study, we present the polyphasic characterization of a filamentous cyanobacterium, denominated strain ETS-13, isolated from mud biofilms collected in the Euganean Thermal District (Italy). The area is known since ancient times for the presence of thermal springs and muds exploited for the beneficial properties linked to heat, electrolytes, and organic compounds produced by the microbiota. The ETS-13 genome was assembled and annotated, while phylogenetic analyzes were performed using a combined approach based on the 16S rRNA sequence and considering the 16S-23S ITS secondary structures. In addition, morphological, biochemical, and physiological features of the organism were investigated, allowing its classification as a new species of the Kovacikia genus, named Kovacikia euganea, which formed a cluster with other species of Leptolyngbyaceae from thermal environments. Interestingly, the strain was the first isolated in Italy capable of performing Far-Red Light Photoacclimation (FaRLiP) when exposed to far-red light, a feature found in other species of the same genus so far tested for this acclimation and isolated form geographically distant and different environments.